THE POST-APOCALYPTIC WORLD OF GOLDING’S LORD OF THE FLIES (Intent Research Scientific Journal, 2024)
By using an abandoned island as the story's location, William Golding depicts the post-apocalyptic wilderness in his book Lord of the Files. This study will demonstrate how William Golding developed the story's characters to represent the general state of destruction that pervaded all facets of existence. Above all, a wilderness experience offers a chance to sharpen awareness and identify the self in opposition to the non-self. It serves as a catalyst for reflection, and the best quotes that capture life as it is fundamentally experienced and lived deepen that process. This paper investigated the harm caused by civilization. The conduct of some boys who just so happen to land on a remote island following their evacuation from a conflict zone was examined in the current research. It focused on the boys' abrupt transition to savage behavior. This research illustrated that the boys revert to barbarism when they are not constrained by social mores and regulations, and their battle for survival and dominance exposes the evil side of human nature. It concluded that the post-apocalyptic society of Golding depicts is a meditation on the frailty of civilization and the inherent cruelty and violence that exists in all of us. Golding's "Lord of the Flies" post-apocalyptic society is a chilling depiction of human nature gone naked. The novel's terrifying depiction of civilization's collapse and plunge into savagery serves as a sobering reminder of how brittle social conventions can be.